Lean leadership basics : develop and empower lean leaders to sustain continuous improvement /: develop and empower lean leaders to sustain continuous improvement. (2021) - Meyers, Michael; Protzman III, Charles W; Protzman, Daniel; Keen, William; Barbon, Davide; Owens, Cliff
No abstract available